International cruise research advances and hotspots: Based on literature big data - Meng, Shuhan; Li, Hua; Wu, Xianhua (Frontiers in Marine Science, 2023)
This paper makes a systematic visual analysis of cruise research literature collected in science network database from 1996 to 2019. The results show that: the overall number of published literatures on cruise research are growing; North American states, Europe, and Asia are the main regions of cruise research. The evolutionary of theme development of cruise research has three stages, and the current hot topics of cruise research can be summarized as cruise tourism, luxury cruises, cruise passengers, destination ports, environmental and biological conservation, and cruise diseases. Future research in the cruise field is in the areas of cruise supply chain, technology in cruise, children’s cruise experience, itinerary design, planning and optimization, brand reputation and luxury cruises, public transportation in destinations, environmental responsibility of passengers and corporate social responsibility, optimization of energy systems, climate change in relation to the cruise industry, the Chinese cruise market and risk management of cruise diseases.